Qualitative studies conducted alongside randomized controlled trials in oncology: A scoping review of use and rigour of reporting. (April 2022) - Thiessen, M.; Harris, D.; Pinches, A.; Vaska, M.; Moules, N.; Raffin Bouchal, S.; Sinclair, S.
Abstract : Background: Randomized controlled trials (RCTs) are the gold standard for generating evidence to inform clinical oncology practice. Knowledge gained through qualitative research methodologies can be complementary to that gained through RCTs. How qualitative research has been combined with RCTs in oncology has not been previously characterized. Objective: This scoping review was conducted to summarize how qualitative research associated with RCTs in the oncology setting has been conducted and examine the quality of reporting. Eligibility Criteria: Manuscripts reporting on qualitative research linked with RCTs in the cancer context that involved patients (both adult and pediatric) and/or informal caregiver (friends/family) were included. Sources of Evidence: Peer-reviewed manuscripts indexed in MEDLINE (OVID) and CINAHL, published in English between 2008 and January 2019. Charting Methods: Formal scoping review methods were followed. A data extraction tool informed by the research questions as well as the COnsolidated criteria for REporting Qualitative research (COREQ) was utilized. Extraction was conducted independently by two authors, with disagreements resolved by a third. Results: Fifty-four articles were included. Assessing information sharing, diet/exercise, and psychotherapeutic interventions were the most common focuses of the RCTs. The most common focus of the qualitative component was on gaining insight into the experience of receiving the intervention or participating in RCT procedures. How the intervention impacted the cancer experience was not a common focus of the qualitative components. Some reports provided insufficient information to understand how the qualitative components aligned with the RCT components. The results of the qualitative and RCT components were not integrated to draw meaningful conclusions about the efficacy of the intervention under study in most cases. Reports focusing on only qualitative methods had higher median (Mdn) reporting of COREQ items compared to reports that included both the qualitative and RCT components (Mdn = 18 vs. Mdn = 14, respectively; p <0.001). Conclusions: This review identified that qualitative research has been combined with RCTs in the cancer context in a number of ways, most commonly to understand the experience of receiving study interventions or participating in trial procedures. Exploring how interventions impact other aspects of the cancer experience is an approach that should be considered in future work. Formalized guidelines for the design and reporting of investigations that combine qualitative and RCT approaches in the cancer context are expected to be of value. Tweetable abstract: Combining qualitative research with randomized controlled trials in oncology: an impornt opportunity for discovery.